The legal characteristic of technical rules - Довженко, Євгенія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
This article provides a general theoretical study of the role and place of the technical rules for the social and the legal regulation of relationships. The author concludes that the social nature of the technical requirements manifests itself through the mechanism of their creation, they can acquire legal value, and also have a legal form of existence. The Technical rules acquire social meaning when they become general rules (norms) and people begin to coordinate their actions with the technical requirements, because such rules always involve specific ratio to them of subjects (groups of) to process of creation of products (goods) and the provision of services. The social nature of the technical rules primarily manifested through the mechanism of their creation, is based on a knowledge of the objective laws functioning and development of the material world for the benefit of people. The technical regulations can take a legal nature when the state formulated the content of the technical and legal regulations by relevant authorities, and compliance with which is recognized legally binding. Also the state can establish legally responsible for violations of content of technical rules. Technical rules interacts with legal rules, helping to define the elements of different misconducts. Technical, technological and other rules may have the legal form of existence as an State Standard. Legal characteristic of technical rules lies in the fact that they are the officially and formally established rules (requirements, rules, regulations, terms, etc.) relating for circle of non-personified or personified humans, that may be compulsory or to have recommendations character, they are acting in time, space and respect to certain objects, and their action terminates or is canceled in the prescribed manner or for a special procedure.